ANALISIS PERLAKUAN ZAKAT PROFESI TERHADAP PERHITUNGAN PAJAK PENGHASILAN ORANG PRIBADI (PEGAWAI TETAP) - Siti Fatimah Azzachrach (Jurnal Universitas Paramadina, 2014)
This paper aims to know a manner of treatment of profession almscalculation regarding to employee’s income tax. This writing also wants tofind out how the implementation of employee’s income tax calculation. Themethodology that use in this paper is descriptive analytical study withcollecting the data through literature review, observation, and interviewconcerning calculation of alms and tax profession by calculating the numberof alms and tax profession value through the preceding data.The result of this research is in calculating alms profession and employee’sincome tax that have calculating alms profession, thus, there is a lowerburden of duties. It is because the alms profession could decrease tax value;therefore, the taxpayer will be in greater condition because of the recalculatingof alms profession by the work supervisor before. According tothe result, the writer expected there will be a rise income in alms and taxsector for the public welfare.